2018
DOI: 10.1016/j.contraception.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid and fulfillment of desired postpartum sterilization

Abstract: Efforts are needed to ensure that Medicaid recipients who desire sterilization receive timely services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…Full study methodology has been published previously [ 10 ]. Briefly, we reviewed each patient’s linked outpatient and inpatient electronic medical record for demographic and clinical characteristics, postpartum contraceptive plan choice, and plan achievement for up to 365 days from date of delivery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full study methodology has been published previously [ 10 ]. Briefly, we reviewed each patient’s linked outpatient and inpatient electronic medical record for demographic and clinical characteristics, postpartum contraceptive plan choice, and plan achievement for up to 365 days from date of delivery.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, after controlling for patient and physician level factors, we have found that the disparity in sterilization completion between patients with Medicaid and private insurance desiring postpartum sterilization is no longer significant [ 7 ]. Rather, Medicaid insurance status may be simply a proxy for other demographic and clinical factors such as adequacy of prenatal care and route of delivery that account for the difference in sterilization for patients with private versus Medicaid insurance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a secondary analysis of a subset of all 8,654 women who delivered at 20 weeks or beyond from January 1, 2012 through December 31, 2014. The primary analysis investigated the subset desiring postpartum sterilization [12]. For the purposes of this secondary analysis, the cohort was restricted to patients who indicated interest in LARC.…”
Section: Methodsmentioning
confidence: 99%
“…For the purposes of this secondary analysis, the cohort was restricted to patients who indicated interest in LARC. Full methodological details have been presented previously [12]. …”
Section: Methodsmentioning
confidence: 99%
“…This policy was enacted in 1974 in response to the unacceptable instances of coerced sterilization of marginalized women [2]. However, in several studies with clinical samples, as few as half of women on Medicaid who desire a postpartum sterilization actually have the procedure, and greater than 20% who do not obtain their desired postpartum sterilization will have a subsequent unintended pregnancy within the following year [3][4][5][6][7]. These unplanned and unintended pregnancies disproportionally impact low-income women of color, adding to the morbidity and mortality of this population [2,8].…”
mentioning
confidence: 99%